Notification and transparency issues in the WTO and the US' November 2018 communication - Aileen Kwa; Peter Lunenborg (South Centre, 2019)
Various WTO Members submitted a Communication to the WTO in November 2018 which, if accepted, would affect the implementation of Members' transparency and notification obligations at the WTO. It would strengthen the already burdensome notification obligations and introduce new punitive administrative measures should obligations not be complied with. This paper provides information about WTO Members' current notification obligations and their level of compliance; looks at the history of discussions on notifications, particularly in the Working Group on Notification Obligations and Procedures which took place in 1995 - 1996; and provides an analysis of the Communication. The analysis focuses on the extent to which the elements are consistent with or go beyond the current WTO disciplines. It concludes that non-compliance with notification obligations is real. However, rather than expanding obligations and introducing punitive measures, constructive and effective solutions should be based on nuancing of obligations in the context of a Special and Differential Treatment approach and through the use of incentives. It also acknowledges that countries with a chronic lack of capacities will continue to struggle with the WTO's complex notification obligations and requirements until they attain higher levels of development and, thus, improved institutional capacities.
Keywords: 300; WTO-Recht; Politische Kommunikation; Normbefolgung; USA